Orbital Apex Syndrome: A Case Series in a Tertiary Medical Center in Southern Taiwan - Lee, Peng-Hsuan; Shao, Shih-Chieh; Lee, Wan-Ju Annabelle (Frontiers in Medicine, 2022)
Background Orbital apex syndrome (OAS) is a rare ocular complication following by infection, inflammation, trauma, neoplasms, and vascularity. The epidemiological features of OAS remained limited, so this study aimed to present ophthalmic clinical features, determine the causes to evaluate the visual prognosis of orbital apex syndrome (OAS) patients in Taiwan. Methods This was a retrospective study by reviewing the electronic medical records from National Cheng Kung University Hospital in Taiwan during 2017–2019. We included patients diagnosed with OAS to review their ocular symptoms and signs, visual acuity, ocular images, etiologies, treatment and visual prognosis. Results Twenty cases (mean age: 65.55 ± 13.06; male: 75%) with the diagnosis of OAS were included in this study. All patients presented as unilateral involvement, but the initial ocular presentations and etiologies varied. For example, blurred vision was reported in 80% of these patients, and tumor-related compression (55%) and infection (15%) were the most frequent causes for the OAS. After the follow-up, we found 35% of patients' visions declined or worsened to the blindness, 15% of patients' visions remained stable, 20% of patients' visions had mild improvement, and 35% of patients' visions were not measured because of debilitating clinical condition. We identified three OAS patients with mortality (15%), and all of them were attributed to the underlying malignancies. Conclusion The clinical magnifications and etiologies of OAS are heterogeneous in Taiwan. Our findings indicated the tumor-related compression is the most frequent causes of OAS in Taiwan, and it is also related to poor clinical outcomes.